2006
DOI: 10.1002/lt.20869
|View full text |Cite
|
Sign up to set email alerts
|

The role of TIPS for portal vein patency in liver transplant patients with portal vein thrombosis

Abstract: The purpose of this research was to study the efficacy and outcomes of transjugular intrahepatic shunt (TIPS) in end-stage liver disease (ESLD) patients with portal vein thrombosis (PVT) eligible for orthotopic liver transplant. Nine consecutive patients with PVT underwent TIPS as a nonemergent elective outpatient procedure. The primary indication for TIPS was to maintain portal vein patency for optimal surgical outcome. Eight patients underwent contrast enhanced computed tomography (CT) and 1 magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 19 publications
1
57
1
Order By: Relevance
“…Previous case reports have validated the safety and efficacy of TIPS in recanalizing the PV system prior to OLT, mainly to allow for patent portal flow at the time of transplantation and reduce the need for intraoperative thrombectomy and risk of rethrombosis [5,[18][19][20][21][22]. Murad et al demonstrated that the degree of extension of thrombosis into the splanchnic venous bed directly correlated with decreased survival [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous case reports have validated the safety and efficacy of TIPS in recanalizing the PV system prior to OLT, mainly to allow for patent portal flow at the time of transplantation and reduce the need for intraoperative thrombectomy and risk of rethrombosis [5,[18][19][20][21][22]. Murad et al demonstrated that the degree of extension of thrombosis into the splanchnic venous bed directly correlated with decreased survival [20].…”
Section: Resultsmentioning
confidence: 99%
“…Although some reports have shown that transjugular intrahepatic portosystemic shunt (TIPS) may be an appropriate therapeutic option for patients with PVT, the data are limited [5][6][7]. Portal vein thrombosis typically occurs within weeks after orthotopic liver transplantation (OLT) and is uncommon, with a reported incidence of 1.2% [8].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies, however, show a high procedural success rates of 73 to 100 %, a relatively low rate of TIPS dysfunction, with a final TIPS patency rate of 57-88 % [95][96][97][98]. Cavernomatous transformation [95][96][97][98], was found to cause increased technical difficulty. Likewise, older thrombi were associated with increased technical failure and a worse clinical outcome [99].…”
Section: Tips For the Treatment Of Pvtmentioning
confidence: 95%
“…Two-year survival rates of about 80 % have been reported [96,97] Survival was better in patients with successful rather than failed TIPS placement [97]. Most available surveys had a retrospective design on patients where the indication for TIPS was not PVT but refractory complications of portal hypertension [95][96][97][98]. In another study [91], seven patients with PVT were treated with a TIPS due to a contraindication to anticoagulation or thrombus progression.…”
Section: Tips For the Treatment Of Pvtmentioning
confidence: 99%
“…In contrast, degree stratification is consistently involved in the studies about outcome of invasive therapies for PVT [5][6][7][8][9] due to its close associations with operability and prognosis. Herein, diverse classifications of PVT were listed in Table 2, except for simple classification into complete and partial thrombus.…”
Section: Degree Of Portal Vein Thrombosismentioning
confidence: 99%